2014
DOI: 10.7162/s1809-48722010000200002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Otorhinolaryngologies' Manifestations in Patients with Pulmonary Tuberculosis

Abstract: Summary Introduction:?The tuberculosis continues being a world problem and in the last years had an increase in his incidence mainly by the growing number of patients with HIV. The tuberculosis has like an etiologic agent the Mycobacterium tuberculosis that possesses a period of latency generally prolonged between the initial infection and the illness. That illness can affect diverse organs and systems. M Method:?This study is descriptive, transversal and prospective. Within, patients diagnosed with pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…The age distribution shows a normal pattern with a peak of 38.4 % in the fourth decade of life. This is as per the distribution reported by Chakravarty et al [1,6]. It has been reported that usually PTB is not associated with EPTB.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The age distribution shows a normal pattern with a peak of 38.4 % in the fourth decade of life. This is as per the distribution reported by Chakravarty et al [1,6]. It has been reported that usually PTB is not associated with EPTB.…”
Section: Discussionsupporting
confidence: 88%
“…Dysphonia is the commonest presenting complaint with pain also being a prominent feature in laryngeal TB [1,[15][16][17][18]. Though all our patients complained of hoarseness, pain was not a chief complaint.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Lymph node TB may result from dissemination via the blood stream, of bacillary pulmonary foci [13], as well as from the bacilli gaining entrance via the tonsils, dental or pharyngeal foci [14]. It is located most frequently in the cervical, supraclavicular and hilar and mediastinal regions.…”
Section: Tb Of Cervical Lymph Nodesmentioning
confidence: 99%
“…It is one of the most prevalent forms of TB in the head and neck. In general, it presents itself insidiously with a gradual increase in the lymph node and evolution to caseification [14].…”
Section: Tb Of Cervical Lymph Nodesmentioning
confidence: 99%